The Influence of Muhammadiyah University Surakarta's Tagline on Audience Brand Awareness and Campus Image - Rachmawati, Amanda Tri; Santoso, Budi (Riwayat: Educational Journal of History and Humanities, 2025)
Competition among universities requires each institution to establish a strong identity that is easily recognizable and has a clear position in the public mind. One communication strategy used is the use of taglines as a representation of the institution's values and character. This study aims to analyze the influence of the tagline of Muhammadiyah University Surakarta (UMS), namely "Wacana Keilmuan dan Keislaman" (Discourse on Science and Islam), on the formation of brand awareness and campus image. This study employs a quantitative approach, utilizing a simple linear regression method with two equation models to investigate the relationship between the tagline variable and brand awareness, as well as campus image. Data was collected through the distribution of questionnaires to respondents who are active students in the Communication Studies program at UMS. The results of the study indicate that the UMS tagline has a positive and significant influence on both brand awareness and campus image, with a probability value of 0.000 (p 0.05) in both models